(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
This paper shows the details of measurement of the acoustical transmission loss of single expansion chamber muffler with various lengths to diameter ratios of cylindrical chamber muffler. A muffler is an important noise control element for reduction of machinery exhaust noise, fan noise, and other noise sources involving the flow of gases. Mufflers are typically arranged along the exhaust pipe as the part of the exhaust system of an internal combustion engine to reduce its noise. Firstly simulation tool results (Comsol) are compared with experimentally then results are observed with various expansion ratio.